Patient's Death From the Perspective of Nursing Students - Szczupakowska, Magdalena; Stolarek, Patrycja; Roszak, Magdalena; Głodowska, Katarzyna; Baum, Ewa (Frontiers in Public Health, 2021)
Introductions: An exceedingly small amount of scientific research concerns the response to patient death among nursing students. There was a need to examine their perspective on the patient's death with which they experience during their studies. Material and methods: The research was conducted in May 2019 using Google form on social media. The 467 nursing students answered questions about their experience with the patient’s death. Results: The subject of the research was how early and how often nursing students meet a patient's death. Authors wanted to check the subjective assessment of students' preparation for the death of a patient and their perception of classes conducted in this area. Conclusions: Nursing students encounter the death of a patient very often and very early. Some of them experience this during the first year. Although the curriculum includes content related to the care of a dying patient, students believe that there is still too little of it and that it does not prepare it in a satisfactory manner.